Assessment of the quality of independent nursing practice in Indonesia based on total quality management indicators - Sahputra, Devi; Lumbantobing, Paul; Tuppal, Cyruz P. (Belitung Raya Foundation, Indonesia, 2021)
Background: The quality of management has become a problem and significant issue of the late decade in Indonesia's professional nursing practice. By implementing total quality management (TQM), the organization would identify a health organization system's performance to improve patient satisfaction and patient safety for independent nursing practice services. Objective: This study aimed to assess the quality of independent nursing practice in Indonesia based on TQM indicators.Methods: This study employed a sequential explanatory mixed methods design. Participants were 105 Chief Executive Officers (CEOs) of independent nursing practices who answered a TQM survey using The Malcolm Baldrige Criteria for Performance Excellence (MBCfPE). The quantitative responses were analyzed using SmartPLS version 3.0. For qualitative data, selected six participants from total respondents were interviewed to explore the participants' understanding of TQM. All the responses were transcribed and uploaded using NVIVO ver. 11 for thematic analysis.Results: Leadership positively influenced strategic planning, customer attention, assessment analysis, and information management (focusing on personnel process management and efficiency) (p <0.001). In addition, process management indicated a positive influence on performance results (p <0.001). Interview transcriptions concentrated on the following themes that emerged, such as quality focus, service focus, human resource focus, performance result, leadership, service system design, strategic planning, and information system.Conclusion: TQM with the adaptation of MBCfPE criteria improves the organization's performance and serves as a strategic component in assessing and implementing sustainability change. The findings of this study can be used by CEOs of independent nursing practices for continuous improvement. In addition, the results serve as a basis for the ministry of health for accreditation to ensure the high quality of health care services.